Human Cord Blood Derived Unrestricted Somatic Stem Cells Restore Aquaporin Channel Expression, Reduce Inflammation and Inhibit the Development of Hydrocephalus After Experimentally Induced Perinatal Intraventricular Hemorrhage - Purohit, Deepti; Finkel, Dina A.; Malfa, Ana; Liao, Yanling; Ivanova, Larisa; Kleinman, George M.; Hu, Furong; Shah, Shetal; Thompson, Carl; Joseph, Etlinger; Wolin, Michael S.; Cairo, Mitchell S.; et al. (Frontiers in Cellular Neuroscience, 2021)
Intraventricular hemorrhage (IVH) is a severe complication of preterm birth associated with cerebral palsy, intellectual disability, and commonly, accumulation of cerebrospinal fluid. Histologically, IVH leads to subependymal gliosis, fibrosis, and disruption of the ependymal wall. Importantly, expression of aquaporin channels 1 and 4 regulating respectively, secretion and absorption of cerebrospinal fluids is altered with IVH and are associated with development of post hemorrhagic hydrocephalus (PHH). Human cord blood derived unrestricted somatic stem cells (USSCs), which we previously demonstrated as having anti-inflammatory effects, were injected into the cerebral ventricles of rabbit pups 18 hours after glycerol-induced IVH. USSC treated IVH pups showed a reduction in ventricular size when compared to control pups at 7 and 14 days (both, p < 0.05). Histologically, USSC treatment reduced cellular infiltration and ependymal wall disruption. In the region of the choroid plexus, immuno-reactivity for AQP1 and ependymal wall AQP4 expression were suppressed after IVH but were restored following USSC administration. Effects were confirmed by analysis of mRNA from dissected choroid plexus (CP) and ependymal tissue. TGF-β isoforms’ and MMP-9 mRNA as well as protein levels were significantly increased following IVH and restored towards normal with USSC treatment (p < 0.05). The anti-inflammatory cytokine IL-10 mRNA was reduced in IVH, but significantly recovered after USSC injection (p < 0.05). In conclusion, USSCs exerted anti-inflammatory effects by suppressing both TGF-β specific isoforms, CTGF and MMP-9, recovered IL-10, restored AQP1 and AQP4 expression, and reduced PHH. These results support the possibility for USSC use to reduce IVH consequences in prematurity.